Antecedents of Revisiting Intention for Natural Tourism Destinations in the Context of Muslim Societies - Fauzi, Daffa Redika; Hadi, Prisilia; Roselawati, Fiona; Yustisia, Sofie Dhinar; Mutmainah (Lentera Barasaki Publishing House, 2023)
The collaboration of nature tourism with religiosity is currently one thing that needs to be considered in sufficient detail. This can be seen by the development of halal tourism, but so far research that discusses halal tourism from the point of view of natural tourism destinations still has inconsistent results, so further research is needed with the aim of answering the inconsistency of these results. This study focuses on discussing natural tourism destinations from the point of view of halal tourism by placing the variables destination image, destination trust, service quality, destination attractiveness, towards revisit intention. This research is a survey research with respondents as many as 115 people who have visited natural tourist destinations in Banyumas, Central Java, Indonesia in the last 6 months. The results showed that destination image and destination trust proved to have a positive effect on revisit intention. However, destination trust and service quality have no effect on revisit intention.